Understanding the effects of social media fake news on consumers’ brand trust and purchase intention - Chen, Zi Ying; Law, Zi Yan; Liew, Xin Ci; Ong, Xuan Wen; Sarah, Xavier Anthony (2023)
The development of fake news had a significant impact in many areas, including politics, health, and beauty. The influence of fake news on social media has been discussed in different fields. However, the social media fake news on consumers’ brand trust and purchase intention in the food and beverage industry is limited. The study aims to fulfill three primary objectives: firstly, to explore the effects of social media fake news on brand trust among consumers, secondly to analyse the effects of social media fake news on consumers’ purchase intention and lastly, to investigate the effects of the level of exposure to fake news on consumers’ brand trust and purchase intention. This qualitative study employed in-depth interviews with 20 undergraduates of different race, gender, and age. These 20 were also separated into two groups: heavily exposed and less exposed, in light of cultivation theory. The thematic analysis approach was used to analyse the data. Furthermore, the findings are that fake news needs to be supported by some moderating factors to effect consumers brand trust and purchase intension. Besides that, Stimulus-Organism-Response framework was also used in this paper as (S) - fake news, (O) - health concern, (R) - affect brand trust and purchase intention. This research helped understand the effect of social media fake news on consumers’ brand trust and purchase intention in the food and beverage industry.